Antibacterial Test of Dadih Against Pathogenic Bacteria and Its Effects on Native Chicken Immunity Organs - Ginting, Nurzainah; Yunilas; Mirwandhono, Edhi; Lin, Y. Y. (Indonesian Journal of Agricultural Research, 2024)
Dadih contains lactic acid bacteria that are antimicrobial so that it can be utilized to maintain the health of poultry such as native chickens. This study aims to prove the ability of dadih to suppress the growth of pathogenic bacteria, namely Staphylococcus aureus, Escherichia coli and Salmonella. This study will also try to find out invivo effect of dadih on the organ immunity of native chicken infected with Salmonella. Antimicrobial research uses disc diffusion method with antimicrobial zone parameter. The invivo study was conducted using a completely randomized design with 4 treatments and five replications where the parameter was the development of immunity organs namely thymus, bursa fabrisius and spleen. The results showed that the antimicrobial test of dadih against Staphylococcus aureus, Escherichia coli and Salmonella caused a zone of inhibition of 7.84, 6.63 and 8.34 mm. Dadih treatment significantly affected the percentage of thymus, bursa fabrisius and spleen. As conclusion that dadih is able to suppress the growth of Staphylococcus aureus, Escherichia coli and Salmonella at medium strength with a range of inhibition zone between 6.63-8.34.Â  Dadih is also able to maintain the health of native chicken.